Determinan Kepatuhan Wajib Pajak UMKM Di Kabupaten Kudus - Nita Andriyani Budiman; Firda Novi Antika; Sri Mulyani (Jurnal Kajian Akuntansi dan Auditing, 2021)
The purpose of this study was to determine the effect of tax officer service quality, tax sanctions, tax compliance costs, tax socialization, and financial conditions on taxpayer compliance at MSMEs in Kudus Regency. The population used in this study were the owners of MSME in Kudus Regency, amounting to 14,941 MSMEs. The sampling method used purposive sampling to obtain 185 respondents. The statistical method used is the Structural Equation Model with processing assistance using Amos 24. The result of the study show that tax officer service quality, tax sanctions, and tax sosialization have a positive effect on taxpayer compliance, while tax compliance costs and financial conditions does not affect on taxpayer compliance. Keywords: Tax officer service quality, tax sanctions, tax compliance costs, tax sosialization, financial conditions, and taxpayer compliance